Integration of Technologies in Daily Life in Smart Homes: A Bibliometric Approach - Giraldo, Luis Fernando Garcés; Valencia-Arias, Alejandro; Suárez-Pizzarello, Marianella; Flores, Eduar Antonio Rodríguez; Rodríguez-Correa, Paula Andrea; Cardona-Acevedo, Sebastián; Ohcoa, José Alexander Velásquez (Journal of Posthumanism, 2025)
This paper aims to analyze research trends related to the integration of technologies in smart homes, which aims to improve the quality of life by automating and connecting devices and systems in the home environment. The study highlights significant gaps in this area. The methodology proposes a bibliometric analysis based on the PRISMA-2020 methodology, in Scopus and Web of Science. The results show a peak of interest in 2016 and 2015, with linear growth. Cook DJ is the primary reference in this field. The research has shifted towards concepts such as automatic resolution and blockchain, with emerging keywords including the Internet of Things and artificial intelligence. The keyword classification indicates a research agenda focused on key concepts. The conclusions provide a comprehensive view of the current landscape and future trends in research, offering valuable guidance for researchers and professionals in the field.